2016
DOI: 10.1155/2016/9526251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetite Aggregate and Steel Powder on Thermal Conductivity and Porosity in Concrete for Nuclear Power Plant

Abstract: Among many engineering advantages in concrete, low thermal conductivity is an attractive property. Concrete has been widely used for nuclear vessels and plant facilities for its excellent radiation shielding. The heat isolation through low thermal conductivity is actually positive for nuclear power plant concrete; however the property may cause adverse effect when fires and melt-down occur in nuclear vessel since cooling down from outer surface is almost impossible due to very low thermal conductivity. If conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Compared to barite aggregate, magnetite has lower thermal conductivity, however, it still has a higher thermal conductivity than normal aggregate. As reported by the authors of Reference [ 37 ], the thermal conductivity of magnetite aggregate is in the range of 6–23 W/m.K, while for normal aggregate it is in the range of 1.3–2.8 W/m.K at ambient temperature which would explain the minor crack propagation for HWSCCs at higher temperatures (i.e., 900 °C) compared to SCC. Higher thermal conductivity results in a better heat transfer, and consequently will reduce thermal stresses within the concrete, which are originated from the temperature gradients between the inner and outer surfaces of the concrete structure exposing to high temperature.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Compared to barite aggregate, magnetite has lower thermal conductivity, however, it still has a higher thermal conductivity than normal aggregate. As reported by the authors of Reference [ 37 ], the thermal conductivity of magnetite aggregate is in the range of 6–23 W/m.K, while for normal aggregate it is in the range of 1.3–2.8 W/m.K at ambient temperature which would explain the minor crack propagation for HWSCCs at higher temperatures (i.e., 900 °C) compared to SCC. Higher thermal conductivity results in a better heat transfer, and consequently will reduce thermal stresses within the concrete, which are originated from the temperature gradients between the inner and outer surfaces of the concrete structure exposing to high temperature.…”
Section: Resultsmentioning
confidence: 79%
“…Moreover, for HWSCC75 and HWSCC100 the initial increase in the elastic modulus occurred at a higher temperature compared to the control SCC sample and HWSCC50. A higher thermal conductivity of magnetite aggregates than cement and air in the filling of pores within the cement matrix can well explain the more significant initial increase of modulus of elasticity for HWSCCs and HWHSC50 [ 37 ]. Increasing the magnetite content, especially with a smaller particle size, leads to the filling of pores and a more compact microstructure.…”
Section: Resultsmentioning
confidence: 99%
“…Research on the influence of magnetite aggregate on concrete porosity was conducted, among others, by [ 37 , 38 ]. Jóźwiak-Niedźwiedzka et al [ 37 ] showed that the total pore volume evaluated by MIP was influenced by the content of magnetite aggregate in concrete.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…[6] Овај тип бетона има велику примену у изградњи нуклеарних електрана, због високог нивоа заштите од зрачења. Услед повећаног ризика од експлозија, када долази до великог ослобађања енергије, неки аутори предлажу и додатно повећање топлотне проводности оваквих бетона [8]. У састав нормалних бетона најчешће улазе компактни агрегати, па њихова порозност зависи највише од процеса хидратације употребљеног цемента.…”
Section: подела бетонаunclassified